2014
DOI: 10.1089/ars.2013.5219
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Regulates Angiogenesis: Effect on Endothelial Cells, Bone Marrow-Derived Proangiogenic Cells and Hind Limb Ischemia

Abstract: Aims: Nuclear factor E2-related factor 2 (Nrf2), a key cytoprotective transcription factor, regulates also proangiogenic mediators, interleukin-8 and heme oxygenase-1 (HO-1). However, hitherto its role in blood vessel formation was modestly examined. Particularly, although Nrf2 was shown to affect hematopoietic stem cells, it was not tested in bone marrow-derived proangiogenic cells (PACs). Here we investigated angiogenic properties of Nrf2 in PACs, endothelial cells, and inflammation-related revascularization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 55 publications
(74 reference statements)
5
69
1
Order By: Relevance
“…This is of relevance to the recent widely investigated involvement of HO-1 in stem cell differentiation [reviewed in Kozakowska et al (7)]. Both HO-1 and Nrf2, its upstream transcription factor, are necessary also for survival, proliferation, migration, and differentiation of cells previously called endothelial progenitor cells, being, in fact, rather proangiogenic monocytes, as demonstrated in the two original articles published in this Forum (3,5). We believe those works may add to several previous studies indicating the significance of HO-1 in blood vessel formation in reparative processes, which may partially depend on those cells [reviewed in this Forum: (1, 2)].…”
Section: Antioxidants and Redox Signalingsupporting
confidence: 53%
See 1 more Smart Citation
“…This is of relevance to the recent widely investigated involvement of HO-1 in stem cell differentiation [reviewed in Kozakowska et al (7)]. Both HO-1 and Nrf2, its upstream transcription factor, are necessary also for survival, proliferation, migration, and differentiation of cells previously called endothelial progenitor cells, being, in fact, rather proangiogenic monocytes, as demonstrated in the two original articles published in this Forum (3,5). We believe those works may add to several previous studies indicating the significance of HO-1 in blood vessel formation in reparative processes, which may partially depend on those cells [reviewed in this Forum: (1, 2)].…”
Section: Antioxidants and Redox Signalingsupporting
confidence: 53%
“…However, their progenitor/stem cell nature is currently the matter of strong debate and new data indicate that those bone marrow cells have to be considered rather as proangiogenic cells (PACs), not having the special stem cell properties. Moreover, two studies published in this Forum (3,5) indicate that PACs may not contribute (directly) to inflammation-driven revascularization. Interestingly, despite the impairment of their mobilization from bone marrow, as evidenced in the Nrf2-knockout mice, the regeneration of blood vessels after hindlimb ischemia was, in fact, accelerated in those mice in comparison with wild-type individuals (3).…”
Section: Antioxidants and Redox Signalingmentioning
confidence: 98%
“…We confirmed an increased level of VEGF-A expression in LTC and demonstrated that this expression was dependent on Nrf2 activation. In addition, Nrf2 participates in endothelial and cancer-associated angiogenesis (43,102,103). We therefore propose that inhibition of Nrf2 could inhibit KS-associated angiogenesis.…”
Section: Fig 11mentioning
confidence: 92%
“…Furthermore, a recent study demonstrated that Nrf2 activates genes involved in the pentose phosphate pathway, which is necessary for DNA and RNA synthesis during cell proliferation (42). Finally, Nrf2 has been shown to aid in cell proliferation by augmenting PI3K/Akt signaling, inhibiting apoptosis through Bcl-2 and Bcl-xL induction, creating an angiogenic environment through HIF-1 and vascular endothelial growth factor (VEGF) expression, and participating in cell migration or invasion by altering matrix metallopeptidase 9 (MMP9) expression (42)(43)(44)(45)(46)(47).…”
mentioning
confidence: 99%
“…Nrf2 contributes to the protection of tissues from damage induced by the outside environment, including damage arising from inflammation, trauma, ischemia, hemorrhage and cancer (18,19). Other studies have identified an association between Nrf2 and angiogenesis (20) and it was demonstrated that the absence of Nrf2 may suppress cancer cell angiogenesis and migration in vivo and in vitro (21)(22)(23). However, the association between DAVF and Nrf2 in the pathogenesis of DAVF remains unclear.…”
Section: Introductionmentioning
confidence: 99%